Flower shape, size and color preferences of four pollinators (Insecta: Apidae) in selected areas of Dhaka city (Bangladesh Journal of Zoology, 2024)
The flower shape, size and color preferences of four bee species belonging to the family Apidae was observed. The observed species were Apis cerana Fabricius, Apis dorsata Fabricius, Apis florea Fabricius, and Xylocopa aestuans Linnaeus. The bees were observed and collected from two areas of Dhaka city- Curzon Hall and Ramna Park from February 2022 to December 2022. During the study period it was observed that the abundance of A. florea was the highest (about 35.18% of the total population) and X. aestuans was the least (about 10.26% of the total population). Preference over a particular size was an important attribute among pollinators. Flowers with mean diameter greater than 50 mm (Dahlia sp., Couroupita guianensis, Tagetes sp. Calendula officinalis, Mesua ferrea) were more visited by the pollinators. Flowers of different shapes were examined in the study and pollinators showed different preferences for different shaped flower. A. cerana mostly preferred rounded and rotate shaped flowers (Dahlia sp. 45% and C. sulphureus 41.16%). A.florea had a preference towards the star shaped flower (L.indica, 69.39%) followed by globe shaped flower (Tagetes sp., 50.70%). A. dorsata had a choice over trumpet shaped flower (Tecoma stans, 35.5%), followed by rounded shaped flower (Dahlia sp. 22%). X. aestuans had preferred orchid shaped flower the most (Bauhinia sp., 30.45%) followed by cruciate shaped flower (M. ferrea, 22.91%). Preference for any particular color was also examined in the study. Among them, A. cerana preferred the red color most (about 45% relative abundance in Dahlia sp.) followed by the color orange (about 41.16% relative abundance in C. sulphureus). A. dorsata preferred the yellow color the most (35.5% relative abundance in T. stans) followed by the color red (22% in Dahlia sp.). A. florea had a preference for color pink (69.39% in L. indica and 46.45% in C. guianensis) followed by the color orange (Tagetes sp., 51.61%). X. aestuans preferred the purple color most in the study (30.45% in Bauhinia sp.). The correlation between proboscis length of pollinators and different floral parameters of flowers were also investigated. The results showed that those parameters were not significantly correlated.Bangladesh J. Zool. 52(1): 27-37, 2024